PENGARUH PERBEDAAN LABA AKUNTANSI DAN LABA PAJAK TERHADAP MANAJEMEN LABA DAN PERSISTENSI LABA - Achmad Fajri, Sekar Mayangsari (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2012)
This study was conducted to examine the effect of book tax-differences in indicating the earnings persistence by first testing whether the listed companies manage their earnings to avoid losses. The number of samples used in this study is 79 firms to examine earnings management, and 26 firms to examine earnings persistance.The results show that samples manage their earnings to avoid losses. In addition, it is evident that the deferred tax expense and accruals jointly influence positively on the probability the company do earnings management. Partially large book-tax differences, operating cash flow, earnings and profit effect significantly on earnings persistence. The results also show that companies with large positive-book tax differences are shown to have lower earnings persistence than firms with small book tax differences. Moreover, companies with large positive book-tax differences show that the persistence od accruals for future earnings is lower than small firms with positive book-tax differences.